Rude Awakenings: Overcoming the Civility Crisis in the Workplace - Jane Honeycutt (Journal of Applied Communications, 2003)
A review of Rude Awakenings: Overcoming the Civility Crisis in the Workplace, by Giovinella Gonthier with Kevin Morrissey